Immunization of pregnant cows with (coligen) to prevent colibacillosis in calves - O.AL-Jiburi ‎, K.; A. Khalifa‎, K. (The Iraqi Journal of Veterinary Medicine, 1986)
This study was undertaken to evaluated vaccinating pregnant cows with "coligen" produced by "Fort Dedge Co." against colibacillsosis in newly born calves. The vaccine was given twice in the last two months of pregancy. Another group of pregnant cows were used as a control. Titration of antibodies was done in the sera and colostrum of the vaccinated and controlled animals and also in the sera of the newly born calves. There was significant rising in antibodies (P<0.01)in the vaccinated animals. These antibodies were protective. Calves receiving colostrum from vaccinated animals were to a certain degree protected aginst colibacillosis. Challenge experiment showed that 36 out of 43 calf of the control group developed diarrheal condition and five of them died. In comparison, 11 out of 653 calf of the vaccinated animals developed mild diarrhea. re is recommended to use this vaccine in Iraq.